Commercial orcharding in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts and Honours in Geography at Massey University, New Zealand - Fielding, G. J (Massey University, 1957)
In recent years commercial orcharding in New Zealand has assumed a new form. Fruit exports are growing year by year and orchard production has become concentrated within certain districts. Alongside this change, and in part responsible for it, has been the formation of grower organizations. Indeed, New Zealanders are fast becoming aware that there is a fruit industry developing in this coutry which, even though limited in prospects, will be a worth-while contributor to our primary production. It is with the view of providing an accurate picture of the present character of the industry that this thesis is presented. The purpose of this investigation will be achieved if it helps to give a broad view of the industry as it differs from place to place, and if it succeeds in inducing those interested in the industry to undertake a systematic stocktaking and review of the elements which underlie these differences before embarking on any scheme of future development. [From Introduction]
Keywords: Orchards; New Zealand